The kissing bridge [large type] - Goyer, Tricia (Goyer, Tricia. Seven brides for seven bachelors., 2014)
Caught between a stifling Amish community and an unnerving outside world, a devout young woman on the run is about to become the newest arrival to West Kootenai, Montana.